Multi-Drug Resistance Combating in Soil Strains of Opportunistic Pathogens by Novel Antimicrobials, Based on Tartaric Acid - Bella G. Babayan; Aram R. Mikaelyan; Nona L. Asatryan; Anna M. Grigoryan; Marina A. Melkumyan (Interdisciplinary Science Studies, 2024)
Antimicrobial resistance and especially multi-drug resistance is one of the most actual problems of modern medicine, agriculture, veterinary and ecology. The initial source of that property is the native bacterial microflora of environment. That is why the study of novel classes of antimicrobial drugs extremely actual goals of modern pharmacology. In current research the seven new synthetic imides and complex amino salts of tartaric acid are considered as potential alternative agents for multi-drug resistance combating in pathogens. They have demonstrated the high activity against some native bacterial opportunistic pathogens and phytopathogens. Also, they have shown the selective inactivity against the non-pathogenic microflora of soil and an ability to biodegradation by non-pathogenic bacteria from Pseudomonas chlororaphis group.